2008
DOI: 10.1590/s0103-50532008000500016
|View full text |Cite
|
Sign up to set email alerts
|

Effect of preparation conditions on morphology, drug content and release profiles of poly(hydroxybutyrate) microparticles containing piroxicam

Abstract: No presente estudo foram preparadas micropartículas de poli(hidroxibutirato) contendo piroxicam pela técnica de emulsão-evaporação do solvente. A influência de alguns parâmetros do processo sobre a eficiência de encapsulação do fármaco foi avaliada por meio de um planejamento fatorial do tipo 2 3 . A eficiência de encapsulação do piroxicam variou de 5,5 a 89,8%. Micropartículas ocas e irregulares, contendo cristais de fármaco na superfície, foram obtidas quando se utilizou 5 mL de clorofórmio como fase interna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
18
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 19 publications
7
18
0
Order By: Relevance
“…The study of DOX release kinetics as dependent upon the drug content of the matrix of microparticles showed that drug release rate became almost 1.5 times faster as DOX content of the matrix of microparticles was increased from 1 to 10 %. The results obtained in this study compare well with the data on the release kinetics of gentamicin from P3HB/ 3HV microparticles [36]; tramadol, piroxicam, and ibuprofen from P3HB microparticles [8,10,11].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The study of DOX release kinetics as dependent upon the drug content of the matrix of microparticles showed that drug release rate became almost 1.5 times faster as DOX content of the matrix of microparticles was increased from 1 to 10 %. The results obtained in this study compare well with the data on the release kinetics of gentamicin from P3HB/ 3HV microparticles [36]; tramadol, piroxicam, and ibuprofen from P3HB microparticles [8,10,11].…”
Section: Discussionsupporting
confidence: 83%
“…At the present time, PHAs are used to prepare microparticles loaded with analgesics [8] and anti-inflammatory drugs; their release kinetics has been studied quite well [9][10][11][12]. PHA microparticles, films, and 3D matrices are promising carriers for antibiotics, enabling the sustained release of the drug [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Prepared microparticles of cellulose acetate butyrate and poly (3-hydroxibutyrate) (PHB) containing piroxicam, in which all formulations studied had around 50% of the total amount of the non encapsulated drug added with the drug content in the microparticles being practically the same, around 15 mg. Prepared piroxicam microparticles using PHB as matrix, and confirmed that the EE% varied from 5.5 to 89.8% [20]. The best encapsulation indices were recorded by preparing polycarbonate microparticles which, under the conditions described in the method, attained an EE% of 95% for the piroxicam.…”
Section: Resultssupporting
confidence: 52%
“…13,14,10 Because of their high biocompatibility and ability to form nanospheres through coacervation, zeins are natural raw materials with potential uses in tissue engineering, drug delivery systems, and biomedicine. 1,15 Biodegradable NPs have received considerable attention because of their potential usefulness in the development of strategies for the topical delivery of oils and therapeutic drugs, [16][17][18] particularly when drug penetration into the dermis is desirable. 19 Most delivery systems with properties suitable for controlled release are microscale beads or gels.…”
Section: Introductionmentioning
confidence: 99%